Cluster randomised controlled trial of tailored interventions to improve the management of urinary tract infections in women and sore throat. Issue 7360 (17th August 2002) - Flottorp, Signe; Oxman, Andrew D; Håvelsrud, Kari; Treweek, Shaun; Herrin, Jeph
Abstract: Objective :To assess the effectiveness of tailored interventions to implement guidelines for urinary tract infections in women and sore throat Design :Unblinded, cluster randomised pretest-post-test trial Setting :142 general practices in Norway Participants :72 practices received interventions to implement guidelines for urinary tract infection and 70 practices received interventions to implement guidelines for sore throat, serving as controls for each other. 59 practices in the urinary tract infection group and 61 practices in the sore throat group completed the study. Outcomes were measured in 16 939 consultations for sore throat and 9887 consultations for urinary tract infection. Interventions :Interventions were developed to overcome identified barriers to implementing the guidelines. The main components of the tailored interventions were patient educational material, computer based decision support and reminders, an increase in the fee for telephone consultations, and interactive courses for general practitioners and practice assistants Main outcome measures :Changes in rates of use of antibiotics, laboratory tests, and telephone consultations Results :Patients in the sore throat group were 3% less likely to receive antibiotics after the intervention. Women with symptoms of urinary tract infection in the intervention group were 5.1% less likely to have a laboratory test ordered. No significant differences were found between the groups for the other outcomes. Large variation was found across the included practicesin the rates of antibiotic prescription, use of laboratory tests and telephone consultations, and in the extent of change for all three outcome measures Conclusions :Passively delivered, complex interventions targeted at identified barriers to change had little effect in changing practice